Pemilihan Smartphone Berdasarkan Rekomendasi Profile User: Integrasi Fuzzy Analytical Hierarchy Process dan Rule Based - Okfalisa Okfalisa; Dwi Utari Iswavigra; Hidayati Rusnedy; Toto Saktioto (Universitas Diponegoro, 2020)
The usability and usefulness of smartphones have been found to lack optimality. Moreover, the action of the customer appears to behave as a consumptive user instead of buying following the basic needs. In selecting the right smartphone, this study provides an alternative option for buyers. The Fuzzy Analytical Hierarchy Process (F-AHP) approach is applied by distinguishing between two distinct decision-making namely, Profile User as a user recommendation-based, and Smartphone-based selection. The suggested requirements are hobbies, areas of jobs, and the use of social network applications in determining the user profile. The weights of the criteria and alternatives for profile users are acquired through the dissemination of questionnaires to 117 respondents. In the meantime, parameters such as Random-Access Memory (RAM), Read-Only Memory (ROM), camera, processor, screen, and battery are added to the smartphone list of criteria upon on the interviews of 15 experts and practices in smartphone and Information Technology (IT). F-AHP rates each of the Smartphone and User Profiles as a first-round output. A rule-based expert system is employed to intertwine Smartphone and User Profiles decision-making viewpoints. The relationship between the Smartphone and the User Profile is therefore circumscribed as the final decision to applaud the acceptable Smartphone for those users of the profile. A prototype of the MatchSmartPhone application has been developed to computerize the F-AHP calculation. This application can be used to assist users according to the user's profile in delivering the best Smartphone device recommendations. Users would be wiser and smarter when shopping in advance.